Evidence for HNRNPH1 being another gene for Bain type syndromic mental retardation. Issue 3 (2nd August 2018) - Pilch, Jacek; Koppolu, Agnieszka A.; Walczak, Anna; Murcia Pienkowski, Victor A.; Biernacka, Anna; Skiba, Paweł; Machnik‐Broncel, Joanna; Gasperowicz, Piotr; Kosińska, Joanna; Rydzanicz, Małgorzata; Emich‐Widera, Ewa; Płoski, Rafał
Abstract : The HNRNPH2 ‐associated disease (mental retardation, X‐linked, syndromic, Bain type [MRXSB, MIM #300986]) is caused by de novo mutations in the X‐linked HNRNPH2 gene. MRXSB has been described in six female patients with dysmorphy, developmental delay, intellectual disability, autism, hypotonia and seizures. The reported HNRNPH2 mutations were clustered in the small domain encoding nuclear localization signal; in particular, the p.Arg206Trp was found in four independent de novo events. HNRNPH1 is a conserved autosomal paralogue of HNRNPH2 with a similar function in regulation of pre‐mRNAs splicing but so far it has not been associated with human disease. We describe a boy with a disease similar to MRXSB in whom a novel de novo mutation c.616C>T (p.Arg206Trp) in HNRNPH1 was found (ie, the exact paralogue of the recurrent HNRNPH2 mutation). We propose that defective function of HNRNPH2 and HNRNPH1 nuclear localization signal has similar clinical consequences. An important difference between the two diseases is that the HNRNPH1 ‐associated syndrome may occur in boys (as in the case of our proband) which is well explained by the autosomal (chr5q35.3) rather than X‐linked localization of the HNRNPH2 gene. Abstract :